KANE’S method for dynamic modeling - Hussain, Zakia; Zainul Azlan, Norsinnira (IEEE, 2016)
Kane’s method is becoming increasingly popular among the dynamists because of its advantages over the Newton-Euler and Lagrange. Many of the literatures have used Kane’s method successfully to model the dynamic systems but none has provided a detailed and quick explanation on how to implement the method on a system. This paper provides a fast and easy guide to learn the Kane’s method, especially for the beginners. A dynamic model of 3 DOF kinematic chain has been developed as an example to demonstrate the detailed steps involved in modeling using Kane’s method. The formulated model is then verified successfully using Lagrange method.